Factors that influence the utilization of maternity services and breastfeeding practices in rural Vietnam - Duong, Dat Van (Curtin University, 2005)
The overall objective of this thesis is to investigate factors that influence the utilization of maternal services, infant feeding and postpartum contraception practices in rural Vietnam. Field studies were carried out in a rural district of Thanh Hoa, a province located in North Central Vietnam. Willingness-to-pay for maternal preferences was measured in a sample of 200 postpartum and 196 pregnant women, as well as 196 men using the payment card technique. An association was found between satisfaction with the quality of maternal services and willingness-to-pay. There were no significant differences in willingness-to-pay values between prenatal and postpartum groups, and between male and female subjects. The feasibility, reliability and validity of a 20-item scale for measuring perceived quality of maternal services provided at commune health centres, were examined based on a sample of 200 postpartum and 196 pregnant women. The instrument was found to have good inter-rater reliability and internal consistency. Maternal status of clients (prenatal vs. postnatal) was found to influence the perceived quality of maternal services. Determinants of the utilization of maternal services at the primary health care level were investigated in a sample of 200 postpartum women together with sixteen focus group discussions and 16 in-depth interviews. The results showed that client-perceived quality of services and socio-cultural, and economic factors, rather than geographical access, could affect the utilization of maternal services. Factors affecting infant feeding practices were measured in a longitudinal study of 463 women at weeks one, 16 and 24 postpartum. Within the first week after delivery, the initiation and exclusive breastfeeding rates were relatively high at 98.3% and 83.6% respectively, but the premature introduction of complementary food was a great concern.Exclusive breastfeeding dropped from 83.6% at week one to 43.6% at week 16, and by week 24, no infant was exclusively breastfed. Home-cooked solid food was introduced by 4.8%, 40.9% and 74.3% at weeks one, 16 and 24, respectively. Logistic regression analysis showed that, together with socio-cultural determinants, factors related to the mother, such as education level and occupation, and infant related factors could influence the initiation and exclusive breastfeeding within six months postpartum. The practice of contraceptive use within six months postpartum was also examined in a prospective study of 463 postpartum women. The proportion of contraceptive users at weeks 16 and 24 were 17.4% and 43.4% respectively. At week 24, of contraceptive users, 57.3% used IUD, 25.1% used condom, and 13.6% used traditional methods. Logistic regression analysis found age, sufficient knowledge on contraceptives and husband/partner opinion can significantly affect the contraception decision. The results of the study indicated that good physical access does not necessarily increase the utilization of maternal services due to institutional, environment and individual barriers. Client-perceived quality of services, socio-cultural and economic factors are important determinants of the utilization of maternal services. In view of the observed low rates of exclusive breastfeeding and contraception, there is a risk of unwanted pregnancy for women within six months postpartum. To improve maternal and child health status, health workers need to be trained in terms of inter-personal communication and counselling skills, and be appropriately supervised by district health authorities. Mobilizing the participation of the community and family, especially men to share the workload with women, would play a crucial role in the improvement of childbirth, contraception and breastfeeding practice.